2016
DOI: 10.15406/mojph.2016.04.00091
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on Tuberculosis among Students of Higher Secondary School, Lalitpur, Nepal

Abstract: The descriptive study conducted to assess the knowledge on tuberculosis among students of higher secondary school, Lalitpur, Nepal was carried out utilizing non-probability purposive sampling technique among +2 students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
1
1
1
Order By: Relevance
“…It is observed that the findings of the present study were acceptable and consistent with the research findings of the previous studies. In present study, all the respondents have acquaintance about tuberculosis and HIV/AIDS from varied sources which was in coherence with the study findings of Sah et al 6 In our study The source of information about TB was teachers (34%) and books (26%) and of HIV/AIDS was TV/radio and means of mass communication (34%) followed by friends and relatives (21%) and teachers (20%). Sah et al in their study among higher secondary school students in Nepal also documented mass media and teachers as the main source of TB information among the respondents.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It is observed that the findings of the present study were acceptable and consistent with the research findings of the previous studies. In present study, all the respondents have acquaintance about tuberculosis and HIV/AIDS from varied sources which was in coherence with the study findings of Sah et al 6 In our study The source of information about TB was teachers (34%) and books (26%) and of HIV/AIDS was TV/radio and means of mass communication (34%) followed by friends and relatives (21%) and teachers (20%). Sah et al in their study among higher secondary school students in Nepal also documented mass media and teachers as the main source of TB information among the respondents.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly Sah et al in their study also reported that there was confusion among the respondents about the type of tuberculosis and less than half (42%) of the respondents knew about the pulmonary form of tuberculosis. 6 In present study Bacteria as causative agent of TB is known to a less percentage of respondents (38.5%) on the contrary Gopichandran et al in their KAP study among high school students in Vellore reported 77.1% awareness among the students as bacteria the causative agent for TB. 11 Singh et al in their study in slum community of Delhi showed only 2.3% respondents claimed TB as caused by germ.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation